Mugwort sensitization and asthma as predictors of food-induced anaphylactic shock in children: a retrospective study in Northern China - Zhou, Zibei; Zhang, Juan; Dai, Nini; Li, Zailing (Frontiers in Allergy, 2025)
IntroductionFood-induced anaphylactic shock is the most severe and life-threatening manifestation of food allergy in children. However, its underlying risk factors remain poorly defined, especially in pediatric populations. This study aimed to identify independent predictors of food-induced anaphylactic shock by analyzing clinical and immunological data from a tertiary hospital in Northern China.MethodsThis retrospective study included 68 children (aged 0–16 years) hospitalized for food-induced anaphylaxis at Peking University Third Hospital from May 2018 to May 2025. Demographic data, clinical manifestations, serum-specific immunoglobulin E (sIgE) levels, and comorbidities were collected. Univariate and multivariate logistic regression analyses were performed to identify independent predictors of anaphylactic shock.ResultsOf 68 patients with food-induced anaphylaxis, 14 (20.6%) experienced anaphylactic shock, with 78.6% of these cases occurring in children older than six years. Wheat and fruits were the most common triggers in the shock group (each 28.6%). Subgroup analysis revealed that 88.9% (8/9) of plant-food-triggered shock cases specifically clustered from April to October, aligning with mugwort pollen season. sIgE levels to inhalant allergens, especially mugwort, were significantly higher in the shock group (P < 0.05). In multivariate analysis, mugwort sensitization (sIgE levels exceeding 2.83 kU/L, OR = 9.91, 95% CI: 1.27–77.31, P = 0.029) and comorbid asthma (OR = 8.11, 95% CI: 1.29–50.98, P = 0.026) were identified as independent predictors of anaphylactic shock.ConclusionsMugwort sensitization and asthma are independent risk factors for food-induced anaphylactic shock in children. Early identification of these risk markers may support early risk stratification and seasonal dietary interventions.